Вивчення особливостей отримання гелів на основі агар-агару для екології, косметології та медицини з антибактеріальними властивостями - Лебедєв, Володимир Володимирович; Мірошниченко, Денис Вікторович; Савченко, Дмитро Олександрович; Мазченко, М. В.; Лєндич, Є. С.; Борісенко, Л. М. (My University, 2021)
The study studies the processes of gelation and features of the rheological properties of agar-agar-based hydrogels in order to obtain modern hydrogels with antibacterial effect. It is shown, that humic acids in polymer hydrogels have a high antibacterial activity, completely stop the formation of mold in them. It is determined, that the most effective in terms of obtaining hydrogels with antibacterial effect are agar-agar compositions with a humic acid content of 15%.
Keywords: антисептичні речовини; гумінові кислоти; гідрогелі; агар-агар харчовий "ДОБРИК"